Vacancy surface migration mechanisms in dilute nickel-chromium alloys. (September 2021) - Startt, Jacob; Deo, Chaitanya; Dingreville, Rémi
Graphical abstract: Abstract: We investigate the unitary mechanisms related to the surface migration of vacancies in dilute Ni-Cr alloys via first-principle calculations. We survey a complete set of surface and sub-surface migration paths for vacancies near the (100) free surface and calculate the corresponding migration barriers. Our results show that a vacancy migrating towards the free surface will face lower energy barriers to migrate via atomic exchange with a neighboring Cr atom rather than with a Ni atom. Once a vacancy reaches the free surface, it will be trapped there. Our results also reveal that, when a Cr atom sits in the atomic plane just below the free surface, any in-plane vacancy hopping jump that would result in the vacancy sitting on top a subsurface Cr atom is energetically unfavorable. Taken together, these fundamental unitary surface migration mechanisms offer insights into the complex interactions between surface segregation and vacancy migration phenomena in Ni-Cr-based alloys.